Predictors of Sudden Cardiac Death in Doberman Pinschers with Dilated Cardiomyopathy. (May 2016) - Klüser, L.; Holler, P.J.; Simak, J.; Tater, G.; Smets, P.; Rügamer, D.; Küchenhoff, H.; Wess, G.
Abstract : Background: Doberman Pinschers with dilated cardiomyopathy (DCM) are at high risk of sudden cardiac death (SCD). Risk factors for SCD are poorly defined. Aim: To assess cardiac biomarkers, Holter‐ECG, echocardiographic variables and canine characteristics in a group of Doberman Pinschers with DCM dying of SCD and in a DCM control group to identify factors predicting SCD. Methods/Animals: A longitudinal prospective study was performed in 95 Doberman Pinschers with DCM. Forty‐one dogs died within 3 months after the last cardiac examination (SCD‐group) and were compared to 54 Doberman Pinschers with DCM surviving 1 year after inclusion. Holter‐ECG, echocardiography, measurement of N‐terminal prohormone of brain‐natriuretic peptide (NT‐proBNP), and cardiac Troponin I (cTnI) concentrations were recorded for all dogs. Results: Volume overload of the left ventricle (left ventricular end‐diastolic volume (LVEDV/BSA) > 91.3 mL/m²) was the single best variable to predict SCD. The probability of SCD increases 8.5‐fold (CI0.95  = 0.8–35.3) for every 50 mL/m²‐unit increment in LVEDV/BSA. Ejection fraction (EF), left ventricular end‐systolic volume (LVESV/BSA) and NT‐proBNP were highly correlated with LVEDV/BSA ( r  = −0.63, 0.96, 0.86, respectively). Generated conditional inference trees (CTREEs) revealed that the presence of ventricular tachycardia (VT), increased concentration of cTnI, and the fastest rate (FR) of ventricular premature complexes (VPC) ≥260 beats per minute (bpm) are additional important variables to predict SCD. Conclusion: Conditional inference trees provided in this study might be useful for risk assessment of SCD in Doberman Pinschers with DCM.